A Novel Method for Increasing the Overheat Ability of Radio Communication Devices with Frequency Hopping Spread Spectrum - Mohammed, Amin Salih; Romanenko, Ihor; B, Saravana Balaji; Kalashnikov, Yevhen; Kuchuk, Nina (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Due to an increase in the number of radio devices with different types of signals and to increase the speed of information transmission, it is necessary to take into account the increase in the probability of erroneous reception of signals as a result of specific disturbances. The investigated methods (techniques) for increasing the noise immunity of radio communication with the FHSS do not take into account the influence of transmitters and fail to predict the load of the radio frequency spectrum. The purpose of this work is the development of the algorithm for the practical implementation of the method of increasing the noise immunity of the radio communication equipment with pseudo randomization of the operating frequency to increase the noise immunity of the radio communication equipment. The essence of the proposed algorithm is the rational distribution of working frequencies between the radio communication devices with pseudo randomization of the operating frequency taking into account the mutual influence of transceivers on each other. According to the results of the research, the application of the methodology based on the proposed algorithm allows to increase the noise immunity of radio communication with pseudorandom interrupt of the operating frequency by an average of up to 30%, depending on the channel state, while an increase in the computational complexity at the level of 10% is noted due to the increase in the number of computational procedures in the method. Thus radio communication systems with the FHSS while working on the basis of the proposed methodology shows an advantage over the known methods.